Effect of Climate Change on Mansonia Mosquitoes Distribution on Filariasis Transmission Potential (Zoonosis) in Pajaten Hamlet, Keleyan, Socah Bangkalan, Madura - Anggraini, Dwi Aprilia; Fahmi, Norma Farizah; Mawli, Rizka Efi; Musthofa, Kamal (Universitas Airlangga, 2024)
This study examines how climate change affects the distribution of Mansonia genus mosquitoes and their potential role in filariasis transmission in Pajaten Hamlet, Keleyan, Socah Bangkalan, Madura, Indonesia. Filariasis is an endemic disease in the area that is spread through mosquito bites and possibly zoonotic transmission. This study examines the biting behavior of Mansonia mosquitoes in bionomics and its relationship with environmental parameters such as temperature and humidity. The results showed an increase in the population of Mansonia mosquitoes in Pajaten Hamlet, especially during the rainy season. Morphological identification revealed the characteristics of Mansonia mosquitoes, with a focus on nocturnal biting behavior. Dissection of adult mosquitoes provided insights into the reproductive process of Mansonia mosquitoes. The influence of climate and environmental conditions on mosquito abundance was also discussed, emphasizing the correlation between mosquito prevalence and factors such as swamp water availability and vegetation. The study also highlights the importance of sanitation in the spread of filariasis and proposes control measures tailored to local conditions. This study conclude that the impact of climate change on the Mansonia mosquitoes spread and emphasizes the need for proactive measures in filariasis control. Control strategies, including habitat clearance, use of bed nets, and deworming of potential reservoirs, are suggested to break the chain of disease transmission. This study makes a valuable contribution to developing effective strategies to control filariasis in the context of climate change.